Pengaruh Kualitas Pelayanan Dan Penyelesaian Klaim Terhadap Kepuasan Pelanggan Pada PT. Asuransi Intra Asia Cabang Jakarta - Angga Saputra; Aldila Rahma Putri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine how the influence of Service Quality and Claim Settlement on Customer Satisfaction of PT. Asuransi Intra Asia, both partially and simultaneously. This research method uses a nonprobability sampling technique where samples are taken by chance, with a sample size of 83 respondents. Data collection techniques using questionnaires, and data analysis techniques are validity tests, reliability tests, simple linear analysis, multiple linear, correlation coefficients, determination coefficients, and hypothesis tests. The results of this study indicate that there is a significant influence between Service Quality and Claim Settlement on Customer Satisfaction of PT. Asuransi Intra Asia simultaneously. This can be seen from the value of the regression equation, namely Y = 4.552 + 0.298 X1 + 0.595 X2. The constant of 4.552 indicates that Customer Satisfaction (Y) will be worth 4.552 if Service Quality (X1) and Claim Settlement (X2) are equal to zero. If other independent variables remain Service Quality increases by 1%, then the Customer Satisfaction (Y) will increase by 0.298. The correlation coefficient value is 0.850 and is positive. where the value is in the interval 0.800-1,000 meaning that the two variables have a very strong relationship. The Determination Coefficient Value is 0.722, so it can be concluded that the variables of Service Quality (X1) and Claim Settlement (X2) have an effect on the Customer Satisfaction variable (Y) of 72.2% while the remaining 27.8% is influenced by other factors. Simultaneous hypothesis testing obtained the calculated F value> F table or (103.959> 3.111), this is also strengthened by the ρ value <Sig.0.05 or (0.000 <0.05). This shows that there is a significant simultaneous influence between Service Quality and Claim Settlement on Customer Satisfaction at PT. Asuransi Intra Asia, Jakarta Branch